A round trip on decentralization in the tourism sector. (September 2018) - Guccio, Calogero; Mazza, Isidoro; Mignosa, Anna; Rizzo, Ilde
Highlights: Use of a quasi-natural experiment to analyse decentralization of tourism policy. Decentralization did not improve the performance of Italian tourism destinations. Unclear allocation of functions leads to inefficiency and institutional conflicts. Need for vertical and horizontal coordination of stakeholders in tourism governance. Overlapping political roles and bureaucracies hinder destination competitiveness. Abstract: Although the performance of the tourism sector has been investigated extensively, the effects of institutional governance have largely been unexplored. This study uses a quasi-natural experiment setting owing to differences in tourism policy devolution between special and ordinary statute Italian regions. Using panel data for the period 1995–2010, we first assess the efficiency of each region by a smoothed bootstrapped Data Envelopment Analysis (DEA) and an order- m frontier estimator. Next, we adopt a difference-in-difference strategy and a fully non-parametric approach to assess whether decentralization affects the performance of regions as tourism destinations. We find that regions affected by decentralization worsened their performance, compared to unaffected regions. The results are robust to different estimators and empirical specifications.